Preparation method for reducing oxygen-silicon atomic ratio of ultra-pure and ultra-fine silicon powder

By reducing the oxygen-silicon atomic ratio of silicon powder, the problem of poor cycle stability and rate performance caused by volume expansion and contraction of silicon-based anode materials in lithium batteries is solved, and higher first-time Coulomb efficiency, cycle life and stability are achieved.

CN119858924APending Publication Date: 2025-04-22HENGYAN (WUXI) NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510038481.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In lithium battery applications, silicon-based anode material has poor cycle stability and rate performance due to excessive volume expansion and contraction.

Method used

Through a preparation method for reducing the oxygen-silicon atomic ratio of ultrapure ultrafine silicon powder, it includes preparing a hydrochloric acid solution in a dispersion tank and stirring and dispersing the silicon powder raw material, adding corrosive agents, and solid-liquid separation and drying, and finally crushing under a protective atmosphere to obtain silicon powder with reduced oxygen-silicon atomic ratio.

Benefits of technology

The generation of lithium oxide and lithium silicate is reduced, the reversible electrode capacity and the increase in polarization during charging and discharging are improved, the first Coulomb efficiency, cycle life and stability are improved, and the cycle stability of lithium batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005236208420000051
    Figure BDA0005236208420000051
Patent Text Reader

Abstract

The invention discloses a preparation method for reducing the oxygen-silicon atomic ratio of ultra-pure and ultra-fine silicon powder, and relates to the technical field of lithium ion batteries. The method comprises the following specific steps: adding a silicon powder raw material into a hydrochloric acid solution in the presence of inert gas, stirring and dispersing for 1-3 hours, adding a corrosive agent, continuously stirring and dispersing for 1-3 hours, carrying out solid-liquid separation, sequentially carrying out filter pressing, washing, filter pressing again, treating for 4-6 hours, drying for 3-5 hours, crushing under inert protective gas after drying, and packaging to obtain the silicon powder with the reduced oxygen-silicon atomic ratio. According to the invention, the controllability of reduction of the atomic ratio of oxygen to silicon in the silicon powder is realized, and the application effect of the silicon powder in silicon-carbon and silicon-oxygen negative electrodes is improved, so that the cycling stability of the lithium battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, in particular to a method for preparing ultrapure ultrafine silicon powder with reduced oxygen-silicon atomic ratio. Background Art

[0002] At present, the negative electrodes of lithium batteries used in the market are basically graphite materials, but due to the defects of graphite materials, the energy density is low and the rate performance is average; silicon, as an ultra-high specific capacity material, can have significant advantages in improving battery energy density with proper addition; the current industry technology routes include nanotechnology, composite material technology, structural design, surface modification, electrolyte optimization, pre-lithiation, porous silicon and alloy silicon (silicon oxygen negative electrode, silicon carbon negative electrode, solid-state battery); however, the excessive volume expansion and contraction of silicon during the charging and discharging process seriously affects the cycle stability and rate performance of the battery. Summary of the invention

[0003] The present invention relates to a link to solve the defects of silicon-based negative electrode materials in lithium battery applications, and indirectly improves the cycle stability of silicon negative electrodes; specifically, it reduces the oxygen-silicon atomic ratio, indirectly reduces the generation of lithium oxide and lithium silicate during application, increases the reversible capacity of the electrode and the increase in polarization during charging and discharging, can provide higher first coulomb efficiency, cycle life and stability, and solve the problems raised in the prior art.

[0004] To achieve the above object, the present invention provides the following technical solutions:

[0005] A method for preparing ultrapure ultrafine silicon powder with reduced oxygen-silicon atomic ratio, specifically comprising the following preparation steps:

[0006] Step 1: prepare a hydrochloric acid solution in a dispersion tank, add silicon powder raw material after connecting to an inert gas, and stir and disperse to obtain a slurry;

[0007] Step 2: adding a corrosive agent to the slurry prepared in step 1, continuing to stir and disperse, and then performing solid-liquid separation to obtain a filter cake;

[0008] Step 3: Dry the filter cake prepared in step 2 under an inert gas, take it out after drying, crush it under a protective atmosphere, and then package it to obtain the silicon powder with a reduced oxygen-silicon atomic ratio.

[0009] Preferably, the temperature of the dispersion tank in step 1 is set at -10 to 10°C; the material contact part of the dispersion tank is lined with plastic or fluorine; the concentration of the hydrochloric acid solution is 5-10%; and the inert gas is one or a combination of nitrogen and argon.

[0010] Preferably, the silicon powder raw material in step 1 is crystalline silicon with a purity of 95-99%, an average particle size of 500nm-20μm, and an oxygen content of 4.8-5%.

[0011] Preferably, the stirring and dispersing time in step 1 is 1-3 hr; and the solid content of the slurry is 10-30%.

[0012] Preferably, the corrosive agent in step 2 is industrial hydrofluoric acid with a mass concentration of 40%; the mass ratio of silicon powder raw material to corrosive agent is 100:(8-10); the corrosive agent needs to be added at one time; and the stirring and dispersing time in step 2 is 1-3 hr.

[0013] Preferably, the solid-liquid separation in step 2 is carried out by filter pressing, water washing and filter pressing again, wherein the filter cloth used for filter pressing has a mesh size of 1000-2000 mesh; and the processing time for solid-liquid separation is 4-6 hours.

[0014] Preferably, in step 3, the drying is performed in a negative pressure drying furnace, the temperature in the negative pressure drying furnace is 200-300° C., and the drying is performed for 4-5 hours; the inert gas during drying is one of nitrogen and argon, or a combination of the two.

[0015] Preferably, the protective atmosphere during the pulverization in step 3 is one or a combination of nitrogen and argon.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] The present invention can achieve controllable reduction of the oxygen-silicon atomic ratio of silicon powder, thereby reducing the amount of lithium oxide and lithium silicate generated during application, increasing the reversible capacity of the electrode and the increase in polarization during the charge and discharge process, so that the silicon powder can be applied to silicon-carbon and silicon-oxygen negative electrodes to improve the initial coulombic efficiency, cycle life and stability, thereby improving the cycle stability of lithium batteries. DETAILED DESCRIPTION

[0018] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0019] The silicon powder raw material in the experiment is crystalline silicon with a purity of 95-99%, an average particle size of 500nm-20μm, and an oxygen content of 4.8-5%;

[0020] The mass concentration of industrial hydrofluoric acid is 40%

[0021] The filter cloth used for filter pressing has a mesh size of 2000 mesh;

[0022] The following chemical reactions occurred in the experiment:

[0023] Si+4HF=SiF4↑+2H2↑

[0024] SiO2+4HF=SiF4(g)+2H2O

[0025] S iF4+2HF=H2↑+S iF6→H2S iF6

[0026] S iF4(g)+H2O(l)→S iO2(s)+4HF(aq)

[0027] Embodiment 1: This embodiment 1 provides a method for preparing ultrapure ultrafine silicon powder with reduced oxygen-silicon atomic ratio, which specifically includes the following preparation steps:

[0028] Step 1: Prepare a 10% hydrochloric acid solution in a dispersion tank at -10°C, connect nitrogen to the bottom of the dispersion tank, add 10kg of silicon powder raw material, stir and disperse for 1 hour to obtain a slurry with a solid content of 20%;

[0029] Step 2: Add 1 kg of industrial hydrofluoric acid to the slurry prepared in step 1 and continue to stir and disperse for 3 hours, then take it out for solid-liquid separation, filter press, wash with water, and filter press again in sequence, the processing time is 6 hours, and a filter cake is obtained;

[0030] Step 3: The filter cake prepared in step 2 is transferred to a negative pressure drying furnace, after nitrogen is introduced, the temperature in the furnace is set to 220° C., and after drying for 5 hours, it is taken out, crushed in a nitrogen atmosphere, and then packaged to obtain the silicon powder with a reduced oxygen-silicon atomic ratio.

[0031] Example 2: Referring to Example 1, the stirring and dispersing time after adding hydrofluoric acid was adjusted, and the specific steps are as follows:

[0032] Step 1: Prepare a 10% hydrochloric acid solution in a dispersion tank at -10°C, connect nitrogen to the bottom of the dispersion tank, add 10kg of silicon powder raw material, stir and disperse for 1 hour to obtain a slurry with a solid content of 20%;

[0033] Step 2: Add 1 kg of industrial hydrofluoric acid to the slurry prepared in step 1 and continue to stir and disperse for 1 hour, then take out for solid-liquid separation, filter press, wash with water, and filter press again in sequence, the processing time is 6 hours, and a filter cake is obtained;

[0034] Step 3: The filter cake prepared in step 2 is transferred to a negative pressure drying furnace, after nitrogen is introduced, the temperature in the furnace is set to 220° C., and after drying for 5 hours, it is taken out, crushed in a nitrogen atmosphere, and then packaged to obtain the silicon powder with a reduced oxygen-silicon atomic ratio.

[0035] Example 3: Referring to Example 1, adjust the temperature of the low temperature effect dispersion tank, the specific steps are as follows:

[0036] Step 1: Prepare a 10% hydrochloric acid solution in a dispersion tank at 10°C, connect nitrogen to the bottom of the dispersion tank, add 10kg of silicon powder raw material, stir and disperse for 1 hour to obtain a slurry with a solid content of 20%;

[0037] Step 2: Add 1 kg of industrial hydrofluoric acid to the slurry prepared in step 1 and continue to stir and disperse for 3 hours, then take it out for solid-liquid separation, filter press, wash with water, and filter press again in sequence, the processing time is 6 hours, and a filter cake is obtained;

[0038] Step 3: The filter cake prepared in step 2 is transferred to a negative pressure drying furnace, after nitrogen is introduced, the temperature in the furnace is set to 220° C., and after drying for 5 hours, it is taken out, crushed in a nitrogen atmosphere, and then packaged to obtain the silicon powder with a reduced oxygen-silicon atomic ratio.

[0039] Example 4: Referring to Example 1, the concentration of the hydrochloric acid solution was adjusted, and the specific steps were as follows:

[0040] Step 1: Prepare a 7% hydrochloric acid solution in a dispersion tank at -10°C, connect nitrogen to the bottom of the dispersion tank, add 10kg of silicon powder raw material, stir and disperse for 1 hour, and obtain a slurry with a solid content of 20%;

[0041] Step 2: Add 1 kg of industrial hydrofluoric acid to the slurry prepared in step 1 and continue to stir and disperse for 3 hours, then take it out for solid-liquid separation, filter press, wash with water, and filter press again in sequence, the processing time is 6 hours, and a filter cake is obtained;

[0042] Step 3: The filter cake prepared in step 2 is transferred to a negative pressure drying furnace, after nitrogen is introduced, the temperature in the furnace is set to 220° C., and after drying for 5 hours, it is taken out, crushed in a nitrogen atmosphere, and then packaged to obtain the silicon powder with a reduced oxygen-silicon atomic ratio.

[0043] Comparative Example 1: As a control experiment of Example 1, the stirring and dispersing time after adding hydrofluoric acid was increased, and the specific steps were as follows:

[0044] Step 1: Prepare a 10% hydrochloric acid solution in a dispersion tank at -10°C, connect nitrogen to the bottom of the dispersion tank, add 10kg of silicon powder raw material, stir and disperse for 1 hour to obtain a slurry with a solid content of 20%;

[0045] Step 2: Add 1 kg of industrial hydrofluoric acid to the slurry prepared in step 1 and continue to stir and disperse for 6 hours, then take out for solid-liquid separation, filter press, wash with water, and filter press again in sequence, the processing time is 6 hours, and a filter cake is obtained;

[0046] Step 3: The filter cake prepared in step 2 is transferred to a negative pressure drying furnace, after nitrogen is introduced, the temperature in the furnace is set to 220° C., and after drying for 5 hours, it is taken out, crushed in a nitrogen atmosphere, and then packaged to obtain the silicon powder with a reduced oxygen-silicon atomic ratio.

[0047] Comparative Example 2: As a control experiment of Example 1, the mass ratio of silicon powder to industrial hydrofluoric acid is reduced to 100:7, and the specific steps are as follows:

[0048] Step 1: Prepare a 10% hydrochloric acid solution in a dispersion tank at -10°C, and introduce an inert gas to the bottom of the dispersion tank, then add 10kg of silicon powder raw material, stir and disperse for 1 hour to obtain a slurry with a solid content of 20%;

[0049] Step 2: Add 0.7 kg of industrial hydrofluoric acid to the slurry prepared in step 1 and continue to stir and disperse for 3 hours, then take it out for solid-liquid separation, filter press, wash with water, and filter press again in sequence, the processing time is 6 hours, and a filter cake is obtained;

[0050] Step 3: The filter cake prepared in step 2 is transferred to a negative pressure drying furnace, after nitrogen is introduced, the temperature in the furnace is set to 220° C., and after drying for 5 hours, it is taken out, crushed in a nitrogen atmosphere, and then packaged to obtain the silicon powder with a reduced oxygen-silicon atomic ratio.

[0051] Comparative Example 3: As a control experiment of Example 1, the mass ratio of silicon powder to industrial hydrofluoric acid was increased and adjusted to 100:15. The specific steps are as follows:

[0052] Step 1: Prepare a 10% hydrochloric acid solution in a dispersion tank at -10°C, and introduce an inert gas to the bottom of the dispersion tank, then add 10kg of silicon powder raw material, stir and disperse for 1 hour to obtain a slurry with a solid content of 20%;

[0053] Step 2: Add 1.5 kg of industrial hydrofluoric acid to the slurry prepared in step 1 and continue to stir and disperse for 3 hours, then take it out for solid-liquid separation, filter press, wash with water, and filter press again in sequence, the processing time is 6 hours, and a filter cake is obtained;

[0054] Step 3: The filter cake prepared in step 2 is transferred to a negative pressure drying furnace, after nitrogen is introduced, the temperature in the furnace is set to 220°C, and after drying for 3-5 hours, it is taken out, crushed under a nitrogen atmosphere, and then packaged to obtain the silicon powder with a reduced oxygen-silicon atomic ratio.

[0055] Comparative Example 4: As a control experiment of Example 1, the drying time in step 2 is reduced, and the specific steps are as follows:

[0056] Step 1: Prepare a 10% hydrochloric acid solution in a dispersion tank at -10°C, and introduce an inert gas to the bottom of the dispersion tank, then add 10kg of silicon powder raw material, stir and disperse for 1 hour to obtain a slurry with a solid content of 20%;

[0057] Step 2: Add 1 kg of industrial hydrofluoric acid to the slurry prepared in step 1 and continue to stir and disperse for 3 hours, then take it out for solid-liquid separation, filter press, wash with water, and filter press again in sequence, the processing time is 6 hours, and a filter cake is obtained;

[0058] Step 3: The filter cake prepared in step 2 is transferred to a negative pressure drying furnace, after nitrogen is introduced, the temperature in the furnace is set to 220° C., and after drying for 3.5 hours, it is taken out, crushed under a nitrogen atmosphere, and then packaged to obtain the silicon powder with a reduced oxygen-silicon atomic ratio.

[0059] Detection test

[0060] The silicon materials prepared in Examples 1-4 and Comparative Examples 1-4 were taken and their oxygen content and water content were measured, as shown in the following table:

[0061]

[0062] By comparing the data of Examples 1 and 2 with Comparative Example 1, it can be seen that as the corrosion time increases, the fluorine ions and silicon and silicon natural oxides will recur, resulting in an increase in oxygen content;

[0063] Comparing the data of Example 1 with Comparative Examples 2 and 3, it can be seen that reducing the amount of the etchant will reduce the corrosion effect, and increasing it will also cause repeated reactions, resulting in an increase in oxygen content;

[0064] Comparing the data of Example 1 and Comparative Example 4, it can be seen that reducing the drying time leads to an increase in water content and also increases the oxygen content, which is the sum of silicon oxygen content + water oxygen atoms;

[0065] Comparing the data of Examples 1 and 3, it can be seen that the increase in the internal temperature of the dispersion tank will affect the effect of the corrosive agent, causing the corrosion to be slightly weaker;

[0066] Comparing the data of Examples 1 and 4, it can be seen that slightly reducing the concentration of hydrochloric acid has little effect on the oxygen content;

[0067] In summary, the reduction of oxygen content in silicon powder is the result of the combined ratio of corrosion time, corrosion liquid concentration, water content, etc., rather than a simple proportional relationship; the preparation method provided by the present invention can effectively reduce the oxygen-silicon atomic ratio of silicon powder.

[0068] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing ultrapure ultrafine silicon powder with reduced oxygen-silicon atomic ratio, characterized in that: The specific preparation steps include: Step 1: prepare a hydrochloric acid solution in a dispersion tank, add silicon powder raw material after connecting to an inert gas, and stir and disperse to obtain a slurry; Step 2: adding a corrosive agent to the slurry prepared in step 1, continuing to stir and disperse, and then performing solid-liquid separation to obtain a filter cake; Step 3: Dry the filter cake prepared in step 2 under an inert gas, take it out after drying, crush it under a protective atmosphere, and then package it to obtain the silicon powder with a reduced oxygen-silicon atomic ratio.

2. The method for preparing ultrapure ultrafine silicon powder with reduced oxygen-silicon atomic ratio according to claim 1, characterized in that: In step 1, the temperature of the dispersion tank is set at -10 to 10° C.; the mass concentration of the hydrochloric acid solution is 5 to 10%; and the inert gas is one of nitrogen and argon or a combination of the two.

3. The method for preparing ultrapure ultrafine silicon powder with reduced oxygen-silicon atomic ratio according to claim 1, characterized in that: The silicon powder raw material in step 1 is crystalline silicon with a purity of 95-99%, an average particle size of 500nm-20μm, and an oxygen content of 4.8-5%.

4. The method for preparing ultrapure ultrafine silicon powder with reduced oxygen-silicon atomic ratio according to claim 1, characterized in that: The stirring and dispersing time in step 1 is 1-3 hr; the solid content of the slurry is 10-30%.

5. The method for preparing ultrapure ultrafine silicon powder with reduced oxygen-silicon atomic ratio according to claim 1, characterized in that: In step 2, the etchant is industrial hydrofluoric acid with a mass concentration of 40%; the mass ratio of silicon powder raw material to etchant is 100:(8-10); the etchant needs to be added at one time; and the stirring and dispersing time in step 2 is 1-3 hr.

6. The method for preparing ultrapure ultrafine silicon powder with reduced oxygen-silicon atomic ratio according to claim 1, characterized in that: In step 2, the solid-liquid separation is carried out by filter pressing, water washing and filter pressing again, wherein the filter cloth used for filter pressing has a mesh size of 1000-2000 mesh; and the processing time for solid-liquid separation is 4-6 hours.

7. The method for preparing ultrapure ultrafine silicon powder with reduced oxygen-silicon atomic ratio according to claim 1, characterized in that: The drying temperature in step 3 is 200-300° C., and the drying time is 4-5 hours; the inert gas during drying is one of nitrogen and argon, or a combination of the two.

8. The method for preparing ultrapure ultrafine silicon powder with reduced oxygen-silicon atomic ratio according to claim 1, characterized in that: During the crushing in step 3, the protective atmosphere is nitrogen, argon or a combination of the two.